2023
DOI: 10.1186/s12889-023-15836-z
|View full text |Cite
|
Sign up to set email alerts
|

“We want it to be a culture”: children and young people’s perceptions of what underpins and undermines education-based wellbeing provision

Abstract: Background Provision that aims to promote the social, emotional, and mental wellbeing of children and young people (including their mental health) is increasingly implemented in education settings. As researchers, policymakers, and practitioners explore the complexities of promotion and prevention provision in practice, it is critical that we include and amplify children and young people’s perspectives. In the current study, we explore children and young people’s perceptions of the values, cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Unlike Casas and Gonzáles' (2017) finding of a learning-related world having relatively weaker associations with wellbeing, we found that academic experiences, with the exception of staff-student relationships, displayed equal effects to almost all of the factors in the social domain. Our findings therefore suggested the importance of fostering a positive academic environment (e.g., through proactive and tailored careers education; equitable and fair grading practices) may have equivalent benefits for wellbeing as fostering a positive social environment.This is important as some have suggested that a focus on improving wellbeing may come at the expense of a focus on academic and learning-related aspects of schooling (Heller-Sahlgren, 2018), and that wellbeing and education agendas are often seen as competing (Demkowicz et al, 2023;Littlecott et al, 2018). However, the positive links between learningrelated experiences and wellbeing outcomes found here can help inform whole school interventions, for instance, supporting the idea that these could be curriculum-based interventions (Allen et al, 2022).…”
Section: Implications For Policy and Practicementioning
confidence: 51%
See 1 more Smart Citation
“…Unlike Casas and Gonzáles' (2017) finding of a learning-related world having relatively weaker associations with wellbeing, we found that academic experiences, with the exception of staff-student relationships, displayed equal effects to almost all of the factors in the social domain. Our findings therefore suggested the importance of fostering a positive academic environment (e.g., through proactive and tailored careers education; equitable and fair grading practices) may have equivalent benefits for wellbeing as fostering a positive social environment.This is important as some have suggested that a focus on improving wellbeing may come at the expense of a focus on academic and learning-related aspects of schooling (Heller-Sahlgren, 2018), and that wellbeing and education agendas are often seen as competing (Demkowicz et al, 2023;Littlecott et al, 2018). However, the positive links between learningrelated experiences and wellbeing outcomes found here can help inform whole school interventions, for instance, supporting the idea that these could be curriculum-based interventions (Allen et al, 2022).…”
Section: Implications For Policy and Practicementioning
confidence: 51%
“…In World Health Organization, 1998) and through the perspective of students themselves (Demkowicz et al, 2023). Insights, such as those provided in the current study, into which aspects of this daily life and practice requires change are therefore foundational and disentangling the effects of learning-related and peer-related school experiences may help practitioners and policymakers to identify effective areas of intervention to promote wellbeing in school settings.…”
Section: Implications For Policy and Practicementioning
confidence: 76%
“…In line with this, there is some evidence that adolescents are more likely to complete CBT-based intervenKon modules in a schoolbased, supervised sesng compared to adolescents who are able to voluntarily access the same modules in an online, unsupervised sesng 50 . Even if the intervenKon is being taught as an acer-school club, the power imbalance that exists in schools (and between researchers and parKcipants) may mean young people feel unable to withdraw from the intervenKon 2,51, 52 .…”
Section: Recommendaon 5: Consider Parcipant Dropout and Disengagementmentioning
confidence: 99%